MANAGEMENT ACCOUNTING (AN EVALUATION OF HIVE’S MANAGEMENT ACCOUNTING SYSTEMS) - Bah, Alhassan (2015)
This project is collaboration between the Nottingham University Business School and HIVE; it came about as a result of the former seeking research opportunities for its MBA, and the latter’s interest in improving its management accounting systems. The project focus is to evaluate the management accounting system of HIVE, with the aim of identifying and discussing possible areas of improvements and recommend actionable points. HIVE is a technology based direct marketing company, with resource constraints. The company’s core competence is its technology, and the key assets are human resource. The company uses a U-form unitary structure which divides the business into departments based on functional expertise. Its product offerings are customisable based on a client’s requirements, but mainly evolves around its core technology the “PLATFORM”. Following an action based research over a period of three months, the project found that Sage50 do have the capabilities to provide the bulk of the management information that the executive management needs. However, due to poor implementation and use of its functions, the company has not benefited from its full potential. It was also found that other factors such as 1) inability to identify and accurately define cost centres, 2) the absence of standardised accounting processes and procedures and, 3) weak performance indicators, leading to ineffective decision making. The project also showed that the company does not have in-house accounting expertise, but this is compensated by investment in project management tools and transferable skills in technology. Various costing techniques were reviewed with micro costing and identified as the most accurate and reliable for decision making, which underpins the recommendation of marginal costing and life cycle costing. Marginal costing and life cycle costing was recommended based on relevance and cost benefit analysis; the research shows that marginal costing as compared to absorption costing is more reliable for short-term decisions and cheaper compared to activity based costing. The researchers also recommend that to avoid the pitfalls of previous Sage50 implementation, the company should follow a change management process based on empirical research and championed by a change agent with sufficient authority.